The typology of well-being and imagination on global organization leaders and the wisdom of classical period philosophers - Acar, Pınar; Güngörmez Şeker, Dilek; Yeke, Müge (My University, 2024)
The understanding of well-being and imagination reflected from classical period philosophers to the present day is now the focus of today’s leaders and managers. In the modern management concept there is a continuous constructive and reformative process. While organizations concentrate on organizational subjects such as work/life balance, the positive culture of the organization, emotional welfare, happiness and ideal working environment, there is also a need to reach a stage of awareness for an integrated understanding and responsibility on social equality, social responsibility, ecological order and biodiversity. The aim of our research is to discover how the wisdom and teachings of classical period philosophers are reflected by today’s global organization leaders. In our research, interviews and statements of the leaders of Fortune 500 listed, global companies such as Samsung, Apple, UPS, Airbus, Amazon, Johnson& Johnson and Walmart were collected and used as secondary data. The data analysis was done using Nvivo (version 2020). The results showed that leaders of global organizations adopted the teachings on well-being and imagination of classical period philosophers such as Plato, Aristotle and Socrates and carried the dimensions such as leader’s well-being, imagination, hedonic approach, subjective well-being, emotional well-being (happiness), positive affection, negative affection, cognitive well-being, life satisfaction, eudaimonic approach and psychological well-being.
Keywords: Classical Period Philosophers; Imagination; Leadership; Qualitative Research Methodology; Well-Being